2014
DOI: 10.1242/dev.106229
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-II recruits Armadillo and Dishevelled for Wingless signaling in Drosophila

Abstract: Wingless (Wg)/Wnt signaling is fundamental in metazoan development. Armadillo (Arm)/β-catenin and Dishevelled (Dsh) are key components of Wnt signal transduction. Recent studies suggest that intracellular trafficking of Wnt signaling components is important, but underlying mechanisms are not well known. Here, we show that Klp64D, the Drosophila homolog of Kif3A kinesin II subunit, is required for Wg signaling by regulating Arm during wing development. Mutations in klp64D or RNAi cause wing notching and loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 63 publications
4
27
0
Order By: Relevance
“…Interestingly, a role for Kinesin-II in Wg signaling and the transport of β-cat/Arm was recently reported (Vuong et al, 2014), consistent with a link to microtubules. One hypothesis is that the IFT-A proteins associate with microtubules and play a similar role to Costal-2 (Cos-2)/Kif7 in Hh signaling.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, a role for Kinesin-II in Wg signaling and the transport of β-cat/Arm was recently reported (Vuong et al, 2014), consistent with a link to microtubules. One hypothesis is that the IFT-A proteins associate with microtubules and play a similar role to Costal-2 (Cos-2)/Kif7 in Hh signaling.…”
Section: Discussionsupporting
confidence: 64%
“…However, in cells committed to the osteoblast lineage, osteoblast differentiation was enhanced by β-catenin ( 39 ). In the present study, the disruption of kif3a led to a reduction of Wnt signaling, consistent with the role of kif3a in osteoblasts and prostate cancer cells demonstrated in previous reports ( 11 , 33 , 40 ). Further investigations are required to confirm the role of kif3a in regulating cilia-dependent Wnt signaling in tooth development and repair.…”
Section: Discussionsupporting
confidence: 93%
“…Biochemical and genetic interactions between AR2 and Klp64D also suggest a possible role of individual AR in interacting with specific partner proteins. The entire Arm repeat domain (aa 141-670) binds in vitro to two domains of Klp64D, the coiled-coil domain and the tail domain 11 . AR2 is the only repeat that interacts with the tail domain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Senseless (Sens), a downstream target of Wg signaling, is reduced by Klp64D knockdown using C96-Gal4 (Fig. 2l) 11 when comparing to the control (Fig. 2k).…”
Section: Overexpression Of Ar2 Causes Wing Notching and Inhibits Wg Smentioning
confidence: 97%
See 1 more Smart Citation